Antibacterial and anticariogenic properties of xylitol: a literature review - Guilherme Goulart Cabral de Oliveira; Débora Marinho Teixeira Freires; Simone Gomes de Oliveira; Ana Luiza de Mattos Guaraldi; Sérgio de Carvalho Weyne; Raphael Hirata Júnior (Associação Brasileira de Odontologia, 2018)
Objective: the purpose of this study was to review some properties of xylitol as an antimicrobial agent and the role of this sugar alcohol in the prevention and control of dental caries activity. Material and Methods: the study was based on PubMed scientific papers, in addition of evaluating older researches, to obtain a more complete view of this polyol, encompassing its biochemical, antibacterial, antibiofilm and toxic properties, as well as its different forms of use. Results: the study carried out highlighted the positive characteristics of xylitol in relation to its use in humans and its possible therapeutic use as a substance for the prevention and control of caries disease. Conclusion: It was concluded that, though the scientific documentation that reinforce its efficiency in caries prevention, some authors still do not consider the clinical evidence as satisfactory about the effects of xylitol, and recommend better controlled clinical investigations, especially in relation to the prolonged use of this polyol, in order to provide more conclusive data.